The United Nations Convention on the Rights of the Child in Wales - Jane Williams (Cardiff: University of Wales Press, 2013)
This volume’s origin lies in a conference held in September 2008 at Swansea University on the theme of revisiting visions and rethinking implementation of the United Nations Convention on the Rights of the Child (UNCRC). Developed papers and additional contributions featured in the 2011 edited collection published by Ashgate, The Human Rights of Children, From Visions to Implementation, co-edited by the editor of the current volume and Dr Antonella Invernizzi. That volume includes some examinations of approaches to children’s rights in Wales. But soon after the conference, which coincided withthe State Party hearings on the UK’s third and fourth periodic reports to the United Nations Committee on the Rights of the Child , it became clear that implementation in Wales had acquired prominence and depth which called for consideration in a distinct collection. Even so, at the end of 2008, the extent of progress that would be made in the ensuing years to implement the UNCRC in Wales could not have been imagined. Aided by a combination of poltiical will and a vibrant and influential non-governmental community, in the which the editor and several contributors played a significant role during this period, this progress included the enactment in March 2011 of the Rights of Children and Young Persons (Wales) Measure 2011. This was and remains the UK’s first and only general legislative measure of implementation of the UNCRC. This edited collection tells the story of the Measure, from its pre-history and politicial genesis through to enactment. Contributions explain the content of the Measure and its practical implications, show how the Measure may impact on selected policy areas and explore the ways in which Welsh Ministers will be held accountable for performance of their new duties concerning implementation of the UNCRC in Wales.